Penguatan Moderasi Beragama di Pendidikan Islam Indonesia: Perspektif Rasional - Prasetia, Senata Adi (LP2M UIN Sayyid Ali Rahmatullah Tulungagung, 2025)
This article examines the strengthening of religious moderation in Islamic education in Indonesia through the lens of rationalism, which serves as a conceptual framework for cultivating moderation values. The central questions addressed are how religious moderation can be reinforced in Islamic education and how rationality contributes to shaping a moderate mindset. The study employs a qualitative approach with a library research method, drawing on primary sources such as classical Islamic texts (e.g., works of al-Jabiri, Arkoun, and Fazlur Rahman), secondary sources including books and academic journals, and policy documents issued by the Ministry of Religious Affairs. Data were analyzed using content analysis through stages of data condensation, presentation, and conclusion drawing, validated by source triangulation. The findings reveal that rationalism within Islamic epistemology has the potential to strengthen religious moderation by promoting critical, integrative, and contextual thinking in Islamic education. The implementation of a rational approach is not only relevant for curriculum design but also for developing learning content that emphasizes practical competencies (know-how) and reflective understanding (know-why), beyond mere textual comprehension (know-what). The implications of this study highlight the importance of advancing an Islamic education model grounded in rationalism to foster an inclusive and transformative paradigm, thereby addressing the contemporary challenges of radicalism and blind fanaticism.